Predictors of Radial Artery Occlusion in Patients with Coronary Heart Disease Undergoing Coronary Angiography or Percutaneous Coronary Intervention via Transradial Access - Sumadio, Muhammad Yolandi; Nina Apriyani Harefa; Nova Syafriana; Sitepu, Inri Pepayosa; Syarifuddin, Fairuz (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Background: Transradial approach is currently the most recommended access for coronary angiography and percutaneous coronary intervention (PCI). However, the risk of developing radial artery occlusion (RAO) with this approach is not uncommon. Objective: This study aims to determine the frequency and predictors of RAO in patients undergoing transradial access. Method: This was a prospective study from January 2021 until December 2023. Participants underwent coronary angiography or PCI via transradial access. Radial artery patency was evaluated before and after the procedure. Results: A total of 456 subjects were enrolled for the study. RAO was found in 37 of 456 subjects (8.1%). From the results of the multivariate analysis, it was found that age (p = 0.012), number of catheters used (p = 0.006), and the incidence of hematoma (p < 0.001) were independent predictors of the incidence of RAO. Conclusion: RAO is a common complication of transradial access so identification of high-risk patients, prevention efforts and close follow-up must be carried out to maintain a patent radial artery. Keywords: percutaneous coronary intervention; radial artery occlusion; transradial -- Highlights: 1. Older age, multiple catheter use, and post-procedural hematoma were identified as independent predictors of radial artery occlusion in patients undergoing transradial coronary angiography or PCI. 2. Early recognition of high-risk patients and careful procedural management are essential to prevent radial artery occlusion and preserve long-term radial artery patency